STANDARDIZATION OF THE ANNUAL PLAN AND APPLICATION FOR THE CONTROL OF INDUSTRIAL COMPANIES PERUVIAN - Arrarte Mera, Raúl Alberto (2009)
This article is a product of Labor Research 2004, fully funded by the Consejo Superior de Investigaciones. Intended to demonstrate the need for mandatory use of the technical and the benefits of the implementation of uniform systems of Planning and Control of Utilities, or Master Budget short term for all industrial enterprises located in the country, as an initial step to employment Strategic Business Plan projected the long term. In the global market where the company develops its national activities, has to cope with large firms, a very intense competitive situation and hostile, that just using these tools on a daily basis, but the employer half unknown. Of the benefits you get at the micro level, encouraging healthy competition and improving business efficiency in the national and international level, resulting in further strengthening the business processes of regional integration such as the Andean Community (AC).